496 Stereotactic Electroencephalography is Associated with Reduced Opioid and NSAID Use When Compared to Subdural Grids: A Pediatric Case Series. (1st April 2022) - Hunsaker, Josh; Scoville, Jonathan; Joyce, Evan; Reese, Jared C.; Wilde, Herschel; Arain, Amir; Bollo, Robert J.; Rolston, John D.
Abstract : INTRODUCTION: Opioid administration and consumption along with length of hospital stay can be decreased using minimally invasive surgery (MIS). METHODS: A retrospective chart review was conducted on pediatric patients that underwent surgery for epilepsy mapping using either SEEG or ECoG between 2015-2019. The hospital stay was divided into four distinct time periods and the total amount of opioids, NSAIDs, and pain scores were calculated for each time interval. The total amount of opioids were calculated by converting each type into their morphine equivalents (ME). Pain scores were calculated by using a modified version of the Clinically Aligned Pain Assessment (CAPA) scale. The two groups were then compared using appropriate statistical tests. RESULTS: The study included 40 patients including 31 in the SEEG group and 9 in the ECoG group. The SEEG group consumed significantly less opioids during the hospital stay when compared to the ECoG group (23.6 vs 61.7 MMEs; p=0.041). There were also significant differences in the length of stay (6.9 vs 12.2 days; p=0.002), complications (0% vs 20%; p=0.006), and total NSAIDs consumed (3264.8 vs 12730.2 mg; p=0.002). CONCLUSION: Opioid and NSAID consumption are significantly lower in pediatric patients who undergo epilepsy mapping via SEEG compared to ECoG. These patients also have a significantly shorter length of stay. MIS options should be considered by patients and physicians in order to decrease the overall use of pain medications and expedite patient discharge.